Role of human milk fortifier on weight gain in very low birth weight babies - Verma, Ganesh K.; Yadav, Amitesh (International Journal of Contemporary Pediatrics, 2018)
Background: Poor weight gain and postnatal growth of VLBW neonates continues to be a major problem. Breast feeding with HMF fortification show positive effect on growth. Main objective is to study the weight gain pattern in very low birth weight babies supplemented with HMF. Methods: This is an observational study conducted in NICU, Department of Pediatrics, U.P. Rural Institute of Medical Sciences and research Saifai, India between January 2015- June 2016 for assessing the weight gain pattern in VLBW neonates supplemented with HMF. Results: Maximum number of babies supplemented with HMF achieved the targeted weight in 8-14 days (32.2%) followed by those who attained this weight within 15-21 days (30%), 22-28 days (21.1%), <7 days (13.3%) and >28 days (3.3%) respectively. Mean time taken to achieve the targeted weight was 16.69±7.19 days. Conclusions: We concluded that the supplementation with HMF, can result in a significant increase in growth. We demonstrated that fortification of human milk, with HMF did not cause any measured adverse effects in VLBW neonates.